A randomised controlled trial of gemcitabine hydrochloride plus S-1 combination therapy versus gemcitabine hydrochloride therapy alone in pancreatic cancer patients aged ≥75 years: a study protocol for an open-label randomised feasibility study. Issue 1 (11th February 2018) - Ishii, Hiroshi; Yamashita, Natsumi; Ueno, Makoto; Ohkawa, Shinichi; Saito, Akiko M; Sekimoto, Mitsugu
Abstract : Introduction: In Japan, the age of patients with pancreatic cancer has increased. Combination chemotherapies such as 5-fluorouracil/leucovorin, oxaliplatin and irinotecan therapy and gemcitabine hydrochloride (GEM) +nab paclitaxel therapy have been developed as the standard treatments for young patients with advanced recurrent pancreatic cancer. However, both therapies produce toxicity and their administration is limited by the patients' age or performance status. The efficacy and safety data obtained in the GEST study—a large-scale randomised controlled study conducted in patients with pancreatic cancer in Japan—suggested that GEM +S-1 (GS) combination therapy is a promising candidate for those aged between 75 and 80 years. However, for patients aged ≥80 years, no efficacy or safety data on GS therapy are currently available. Methods and analysis: This open-label, randomised phase II study will involve patients with advanced recurrent pancreatic cancer, aged ≥75 years, with favourable general conditions. Using the electronic data capture system, participants will be randomly allocated to groups with standard treatment (GEM therapy alone) and study treatment (GS therapy). The treatments will be administered until the conditions meet the discontinuation criteria. The primary endpoint is overall survival. Ethics and dissemination: This trial has been approved by the National Hospital Organisation's Central Review Board (H28-NHOD-01). Discussion: This study will reveal if GS therapy could be a standard treatment option for elderly patients with pancreatic cancer, by clarifying its efficacy and safety. Trial registration number: UMIN000025747; Pre-results.